OPTIMIZATION AND EFFICIENCY ANALYSIS OF REAL-TIME PCR FOR LEPTOSPIRA SPP. DIAGNOSIS BASED ON THE LIPL32 GENE - Rohayati; Rizal Pratama Sulaeman; Fusvita Merdekawati; Yuliansyah Sundara Mulia (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Leptospirosis is a widespread zoonotic infection that endangers the health of both humans and animals, particularly in tropical and subtropical regions. Therefore, timely, sensitive and specific laboratory confirmation is essential for early clinical management. The LipL32 gene is a highly conserved virulence factor in pathogenic Leptospira. Real-time PCR provides rapid detection with high sensitivity and specificity. This study optimized real-time PCR conditions by evaluating annealing temperatures (60°C, 61°C, 62°C), primer concentrations (500 nM, 700 nM, 900 nM), and probe concentrations (250 nM, 300 nM). PCR efficiency was analyzed using absolute quantification with serial DNA dilutions (100 to 10⁻⁴). The optimal conditions were 60°C annealing temperature, 500 nM primers, and 300 nM probes. Near-ideal efficiency (97%) was achieved at 60°C with 500 nM primers and 250 nM or 300 nM probes, while 103% efficiency was observed at 61°C with 500 nM primers and 250 nM probes. This optimization enhances Leptospira detection accuracy using real-time PCR.